2017
DOI: 10.1137/17m111300x
|View full text |Cite
|
Sign up to set email alerts
|

Planar Posets Have Dimension at Most Linear in Their Height

Abstract: Abstract. We prove that every planar poset P of height h has dimension at most 192h + 96. This improves on previous exponential bounds and is best possible up to a constant factor. We complement this result with a construction of planar posets of height h and dimension at least (4/3)h − 2.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Let us remark that it is rather remarkable that linear or polynomial bounds can be obtained when assuming that the poset has a planar diagram or a planar cover graph, respectively. Indeed, for the slightly larger class of posets with K 5 -minor-free cover graphs, constructions show that the dimension can already be exponential in the height, as shown in [11]. (This also follows from Theorem 14 below, applied with t = 3.…”
Section: Applicationsmentioning
confidence: 83%
See 1 more Smart Citation
“…Let us remark that it is rather remarkable that linear or polynomial bounds can be obtained when assuming that the poset has a planar diagram or a planar cover graph, respectively. Indeed, for the slightly larger class of posets with K 5 -minor-free cover graphs, constructions show that the dimension can already be exponential in the height, as shown in [11]. (This also follows from Theorem 14 below, applied with t = 3.…”
Section: Applicationsmentioning
confidence: 83%
“…It is in fact suspected that posets with planar cover graphs have dimension at most linear in their height. This was recently proved [11] for posets whose diagrams can be drawn in a planar way; these posets form a strict subclass of posets with planar cover graphs.…”
Section: Applicationsmentioning
confidence: 93%
“…Joret, Micek and Wiechert [17] have recently shown that for fixed t ≥ 3, d(t, h) grows exponentially with h. The best bound to date in the general case is due to Joret, Micek, Ossona de Mendez and Wiechert [16], where they prove:…”
Section: Connections With Structural Graph Theorymentioning
confidence: 97%
“…Joret, Micek, Ossona de Mendez and Wiechert have shown how their results in [16] can be extended to obtain this conclusion. Meanwhile, Kozik, Krawczyk, Micek and Trotter [24] have a much more complicated argument which [17] showed that the c h ≥ 2h − 2.…”
Section: Planar Posets and Dimensionmentioning
confidence: 99%
See 1 more Smart Citation